Designing an E-Commerce Website to Enhance the Purchasing Power of SMEs Based on Augmented Reality (AR) - Muqorobin Muqorobin; Sumadi Sumadi; Tira Nur Fitria (International Journal of Computer and Information System (IJCIS), 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in economic growth; however, they still face challenges in increasing consumers’ purchasing power in the digital era. This study aims to design an Augmented Reality (AR)-based e-commerce website to enhance the purchasing power of MSME products. AR technology allows consumers to visualize and interact with products virtually, providing a more engaging, informative, and realistic shopping experience. The research methodology includes user needs analysis, system design, and the development of an e-commerce website integrated with AR features. The results indicate that the implementation of AR in e-commerce websites can increase consumer trust and purchase intention toward MSME products. Through more detailed and interactive product visualization, consumers are able to make purchasing decisions with greater confidence. Therefore, an AR-based e-commerce website is expected to serve as an innovative solution to improve the competitiveness and purchasing power of MSME products in the digital market.